Physicochemical Characterisation of Abuja’s Municipal Solid Wastes as a Renewable Energy Resource - Paul Ondachi; Idris Ibrahim Ozigis; Musa T. Zarmai (ABUAD Journal of Engineering Research and Development)
Physical and chemical composition analyses of Abuja’s municipal solid waste samples have been carried out in this study. Laboratory procedures were employed to determine the higher calorific value, the proximate analysis and ultimate analysis of MSW samples from selected districts of Abuja metropolis. An analytical methodology was therefore employed to determine whether the city’s MSW will be good resource for energy generation as a strategy for effective waste management. Abuja’s MSW has an aggregate higher heating value of 38.13MJ/kg. Moisture content of less than 8% obtained for all the samples compares very well with values for Nigerian coals. Volatile matter was found to be above than 60% for each samples tested while fixed carbon was determined to be less than 26% for each sample. The MSW samples gave excellent results for ash content of less than 4% when compared to most Nigerian coals with minimum ash content of 10.72%. The ultimate analysis shows the MSW samples compares fairly well with Nigerian coal samples in terms of elemental carbon, the least value being 41.80%. The least value for elemental carbon in most coal samples is 53.27%. Also, the sulphur content of the MSW samples is much less (not higher than 0.15%), compared with the least value of 0.58% for the coal samples. All the factors considered above indicate that the Abuja’s MSW will perform very well as a primary solid fuel when incinerated for energy recovery. The economic significance of this study lies in the confirmation that Abuja’s MSW is a good and cheap source of energy for electric power generation, replacing the expensive fossil fuel sources with their attendant hazardous emission to the environment. This will make the study area to be a cleaner and healthier environment.